INOVASI MODEL PEMBELAJARAN LITERASI DIGITAL YANG EFEKTIF UNTUK MENDUKUNG IMPLEMENTASI SDGS 2030 - Aqiilah, Nargis; Iman, Wafa Wafiatul; Rachman, Ichsan Fauzi (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Innovation in digital literacy learning models is an urgent need to support the implementation of the 2030 Sustainable Development Goals (SDGs). Digital literacy, which includes the ability to access, understand and use information from various digital formats, is very important in the era of globalization. This research uses a literature review method to analyze how digital literacy can be integrated into the education system and society to achieve sustainable development goals. The research results show that the use of information and communication technology (ICT) through E-learning can increase community participation in development. E-learning offers flexibility in time, place and speed of learning, as well as reducing educational costs. However, challenges faced include the need for independent learning motivation, limited internet infrastructure, and difficulties in delivering certain material online. Therefore, collaborative efforts from various parties are needed to overcome these obstacles and maximize the benefits of digital literacy in supporting the 2030 SDGs.